Emphasis on soft skills training in improved learning - Aguinaga Vásquez, Silvia Josefina (2020)
The current scenario presents dizzying changes, which certainly invites not to lose sight of the school and particularly the mater institution like the university, in order to observe in principle, whether or not they are together forming the skills and competences to perform in a society as unlike ours. In this same scenario, there is a hard task of researchers and publications that influence and emphasize soft skills development. In view of this, the objective of this review article is to evaluate the theoretical and methodological quality of the publications through selective and critical study of what the authors argue about the formation of soft skills, also called socioemotional skills, in improving learning, from the analysis of primary, secondary and tertiary sources such as articles, reports, programs and books. Methodological by its nature is a research of descriptive correlational review and focuses particularly on the revision of original scientific articles, theses and reports, using the deductive and inductive method, using analysis and meta-analysis. The review was carried out taking into consideration the selection criterion, the inclusion and exclusion criterion, the time criterion and the search for objective information in indexed journals. Finally, it is concluded that the various publications on soft skills, from the qualitative, quantitative and mixed levels present a thorough analysis of the variables of study in theory and methodology, evidence of the use of techniques and instruments in each of the research and the results of which determine that the development of soft skills contributes significantly to the learning.